PERUBAHAN STRUKTURAL TENAGA KERJA DARI SEKTOR PERTANIAN KE SEKTOR NON PERTANIAN DI PROVINSI LAMPUNG - Okwan Himpuni; Ernan Rustiadi; Setiahadi Setiahadi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2014)
Agriculture is one of the sectors having largest contribution to the economy of Lampung Province. Most of the population categorized in to work forces, are engaged in agricultural sector as a main livelihood. In general, the rate of job opportunity growth is unbalance as compared to the work force growth. Although the job opportunity ofagricultural sector from year to year decreases compared to the job opportunity increases of non-agricultural and industrial sector.  But from economic sector points of view, the employment’s structure in agriculture, in average, is higher than the other economic sectors. Although in the employment’s structure it is higher than the other economic sectors, but the contribution of agricultural sector decreases each years 0.32 percent. This condition is inversely with non-agricultural and industrial sector that are strengthened respectively 0.4 percent and 0.59 percent from year to year. The tendency of economic structural transformation, gives an overview whether the transformation is consistent with region’s potention. Productivity of the agriculture work force is left far behind the productivity of industrial sector and service’s work forcesector. It the trendcan be seen from the comparation of agriculture’s wage rate, it showed an increase but it still lower than the industrial sector. Agricultural labor’s proportion indicates a decreasing trend in each year. This phenomenon has an inverse relation to the non agricultural and industrial labor’s proportions that has increased from year to year. This mean, there is structural transformation of labor of agriculture sector to non-agriculture sector. By using econometric model, it can be identified significant factors influencing to the job opportunity and the influencing factors to the labor structural transformation from agriculture to non agriculture sectorKeywords: Agricultural, labor, job opportunity, transformation, industrial